Role and Importance of Ergonomics in Providing Safety of Work - U., Kurbonov R.; R., Normurodov A. (International Journal on Orange Technologies, 2021)
The article examines the analysis of one of the current problems - the causes and consequences of the occurrence of factors that have a negative impact on the health of workers employed in the production process, an idea of the methods and means of ensuring safety and the efficiency of work is given.